Housing type and secondhand tobacco smoke exposure among non-smoking New York City adults, 2004 and 2013–14 - Shannon M. Farley; John Jasek; Indira Debchoudhury; Kellie Van Beck; Achala Talati; Sharon E. Perlman; Lorna E. Thorpe (Preventive Medicine Reports, 2022)
Secondhand tobacco smoke (SHS) exposure has declined due to smoking reductions, expanding workplace and public smoke-free air laws, and smoke-free housing policy promotion. Population-based studies examining objective SHS exposure biomarkers have documented reductions over time, however non-smoking urban adults are more likely to have elevated cotinine (a metabolite of nicotine) compared with national averages. Evidence suggests residential housing type may impact urban SHS exposure risk. Direct associations between multiunit housing (MUH) and elevated cotinine have been identified among children but not yet examined among adults. We used data from the cross-sectional 2004 and 2013/14 New York City Health and Nutrition Examination Surveys to investigate associations between MUH (single-family versus 2; 3–99; and 100 + units) and likelihood of elevated serum cotinine among nonsmoking adults (2004: n = 1324; 2013/14: n = 946), adjusting for socio-demographics (sex, age, race/ethnicity, education, income) and self-reported SHS exposure variables. Combined and single-year adjusted multivariable regressions were conducted. Elevated cotinine was defined as a serum level of ≥ 0.05 ng/ml. Combined year adjusted multivariable regression analyses found no difference in elevated cotinine by housing type among non-smoking adults. By survey year, elevated cotinine did not vary by housing type in 2004, while non-smoking adults in 3–99 unit buildings were twice as likely to have elevated cotinine compared with single family residents in 2013/14 (adjusted Odds Ratio = 2.55 (1.13, 5.79)). While SHS exposure has declined, relative burden may be increasing among MUH residents. In urban settings with extensive MUH, attention to housing-based policies and programmatic interventions is critical to reducing SHS exposure.